2019
DOI: 10.1016/j.jinteco.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Preferential trade agreements and antidumping protection

Abstract: Are preferential trade agreements (PTAs) stumbling blocks or building blocks towards multilateral trade liberalization? We address this question by investigating the effects of the negotiation and implementation of PTAs on the use of antidumping (AD) (i.e., the most common form of contingent trade protection) by member countries against non-members, as there has been a concurrent surge in regionalism and AD activity since the 1990s. Theoretically-derived empirical predictions are supported by the empirical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…By contrast, Bown and Tovar () provide empirical evidence that MERCOSUR's preferential liberalisation process has led to increased extra‐bloc import protection including AD in the case of Argentina and Brazil. In a similar vein, Tabakis and Zanardi () investigate the effects of the negotiation and implementation of PTAs on the use of AD by member countries against non‐members but generally find a negative relation in this respect.…”
Section: Literature Reviewmentioning
confidence: 95%
“…By contrast, Bown and Tovar () provide empirical evidence that MERCOSUR's preferential liberalisation process has led to increased extra‐bloc import protection including AD in the case of Argentina and Brazil. In a similar vein, Tabakis and Zanardi () investigate the effects of the negotiation and implementation of PTAs on the use of AD by member countries against non‐members but generally find a negative relation in this respect.…”
Section: Literature Reviewmentioning
confidence: 95%
“…One of the reasons is that MFN tariffs are relatively low. Recently, Tabakis and Zanardi (2019) attempted to determine whether preferential trade agreements are building blocks or stumbling blocks towards multilateral trade liberalisation. Based on the empirical analysis of 15 most intense users of antidumping, the authors found the building bloc effect of the preferential trade agreements because they result in fewer antidumping measures against non-member countries.…”
Section: Trade Creation and Diversion Effectsmentioning
confidence: 99%
“…This study is one of only a small number of papers that analyze the effect of PTAs on TTBs. Blonigen (2005), Prusa and Teh (2010), and Tabakis and Zanardi (2019) focus on antidumping. The first considers how NAFTA impacts the use of antidumping by the US.…”
Section: World Trade Reviewmentioning
confidence: 99%